2022
DOI: 10.3389/fphys.2022.882151
|View full text |Cite
|
Sign up to set email alerts
|

BAIBA Involves in Hypoxic Training Induced Browning of White Adipose Tissue in Obese Rats

Abstract: In recent years, obesity has become an important risk factor for human health; how to effectively prevent and reduce the occurrence of obesity is a hot research topic in recent years. Hypoxic training effectively improves abnormalities of lipid metabolism caused by obesity. The current study explored the effects of hypoxic training on BAIBA secretion and white fat browning in inguinal fat in obese rats. Analyses were performed by HPLC/MS/MS—MS/MS, RT-q PCR and western blot methods. The findings showed that 4 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
1
0
0
Order By: Relevance
“…It has been well-established that cold-exposure can induce BAT activation and AT browning in rats and humans [22,[41][42][44][45], which is consistent with the anticipated findings regarding the coldwater (15 o C) protocol. Moreover, hypoxic exercises have also been shown to induce BAT activation and AT in rats [29][30][31], particularly in the inguinal area [28,66], which is consistent with the anticipated findings for the hypoxia protocol, as proof of principle. The anticipated result for the hypoxic protocol is also consistent with the hypothesis by Mu et al, which highlighted the relationship of hypoxic exercise with better AT browning capabilities due to its ability to upregulate irisin and leptin levels [28].…”
Section: Discussionsupporting
confidence: 82%
“…It has been well-established that cold-exposure can induce BAT activation and AT browning in rats and humans [22,[41][42][44][45], which is consistent with the anticipated findings regarding the coldwater (15 o C) protocol. Moreover, hypoxic exercises have also been shown to induce BAT activation and AT in rats [29][30][31], particularly in the inguinal area [28,66], which is consistent with the anticipated findings for the hypoxia protocol, as proof of principle. The anticipated result for the hypoxic protocol is also consistent with the hypothesis by Mu et al, which highlighted the relationship of hypoxic exercise with better AT browning capabilities due to its ability to upregulate irisin and leptin levels [28].…”
Section: Discussionsupporting
confidence: 82%
“…A study including both normal and obese adolescents showed that serum BAIBA levels increased after prolonged exercise (aerobic or resistance) regardless of obesity ( 78 ). This was confirmed by the results of an animal model, in which four weeks of hypoxic training increased BAIBA levels in the gastrocnemius and blood of obese rats ( 79 ). Roberts et al.…”
Section: Exercise Regulates Baiba Synthesis and Metabolismsupporting
confidence: 56%
“…It induces the expression of the uncoupling protein UCP1 (uncoupling protein 1) and activates the nuclear receptor peroxisome proliferator‐activated receptor‐α, which affect fat metabolism and may contribute to changes in adipose tissue function and fat storage, potentially affecting cardiometabolic pathophysiology. 45 …”
Section: Bcaa ‐Regulated Pathways and Cardiometabolic Diseasementioning
confidence: 99%